Performance of Groundplane Shaping in Four-Element Dualband MIMO Antenna - Subuh Pramono; Tommi Hariyadi; Budi Basuki Subagio (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2017)
This work presents performance of groundplane shaping and its effect in four element dualband multiple input multiple output (MIMO) antenna. This proposed four element dualband MIMO antenna consists of four bowtie dipole antenna which operates at 1800 MHz (low frequency) and 2300 MHz (high frequency). This proposed four element dualband MIMO antenna occupies a 270 x 210 x  100 mm3  of FR 4 substrate. We use four types  of groundplane pattern i.e. full groundplane, cornered spatial groundplane,crossed middle groundplane, and spiral groundplane. These various grounplane patterns influence the performance of main parameters of dualband MIMO antenna. Cornered spatial groundplane pattern yields a largest bandwidth (VSWR ≤ 2) 282 MHz or 15.24% of center frequency at low frequency. Full groundplane pattern creates 135.2 MHz at high frequency. In addition, cornered spatial groundplane pattern also generates a lowest VSWR  that  is valued 1.21 at both low frequency and high frequency. The S parameters, basically both cornered spatial and full groundplane pattern produce a better return loss than two others. All four groundplane patterns deliver  equally a mutual coupling parameter.The last, this proposed four element dualband MIMO with various groundplane patterns gives a good farfield properties i.e. gain, radiation pattern, H-E field.